Pengaruh Return On Equity (ROE), Struktur Aktiva, dan Current Ratio (CR) terhadap Struktur Modal Pada PT. Mayora Indah, Tbk Tahun 2015 – 2023 - Shela Julien Septin; Eka Budi Yulianti; Morina Barus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to examine the effect of Return on Equity (ROE), Asset Structure, and Current Ratio (CR) on Capital Structure in the company PT Mayora Indah Tbk, which is listed on the Indonesia Stock Exchange (IDX) for the period 2015–2023. The data used in this study are secondary data obtained from the company’s annual financial reports during the research period. The research employs a quantitative approach, and the data sources are documentary in nature, focusing on publicly available financial statements.The analytical method used is multiple linear regression analysis, with data processing performed using SPSS software. This method allows the researcher to assess the impact of each independent variable on the dependent variable both partially and simultaneously. The results of the partial hypothesis testing indicate that the Return on Equity (ROE) variable has a positive and significant effect on Capital Structure, suggesting that higher profitability encourages the company to utilize more debt financing. On the other hand, the Asset Structure variable shows no significant negative effect on Capital Structure, indicating that the proportion of fixed assets does not play a decisive role in influencing capital structure in this case. Meanwhile, the Current Ratio (CR) has a negative and significant effect, implying that companies with higher liquidity tend to rely less on external debt. Simultaneously, the three variables—ROE, Asset Structure, and CR—have a significant influence on Capital Structure. These findings can serve as a reference for corporate financial management in optimizing capital structure decisions.